WESTERWALD STONEWARE AT KELMSCOTT MANOR: MORRIS, POTTERY AND THE POLITICS OF PRODUCTION. (30th September 2019) - Chitty, Gill; Stocker, David
Abstract : Kelmscott Manor, the country home of William Morris, houses a remarkable collection of ceramics bearing a singular relationship to one of the most influential figures in Victorian cultural history. This study of Kelmscott's collection of German stoneware reveals new interpretations of its production history and fascinating insights into its significance for the cultural context of Morris's work. Based on a complete catalogue, the paper examines the ensemble of approximately thirty pieces of eighteenth- to nineteenth-century Westerwald stoneware, or grès de Flandres, as it was known to Morris and his contemporaries. The Kelmscott group is the largest collection of this material known from an English historic house and has a composite and well-documented provenance. Supplementary material provided as an online appendix contains a fully illustrated, descriptive catalogue. Westerwald pottery of the seventeenth century and earlier has been extensively studied, but its ceramics of the late eighteenth to nineteenth centuries have received little attention. Most accounts stress the simplification of vessel forms and 'degeneration' of decorative designs during this period, leading towards mass-production c 1900. This paper re-assesses later Westerwald output, drawing attention to a vernacular pottery tradition of significant interest in its own right. This paper suggests that it was this continuing tradition of vernacular production and its naturalistic, decorative schemes that attracted the interest of Morris throughout his adult life, from the Red House experiment to the heyday of Morris & Co. Examining his writing on creativity, the minor arts and labour, the paper interprets grès de Flandres as an expression of Morris's idealisation of the relationship between labour and craft production.